2020
DOI: 10.1111/inr.12637
|View full text |Cite
|
Sign up to set email alerts
|

Women‐centred workplace health promotion interventions: a systematic review

Abstract: Aim: To analyse workplace health promotion interventions implemented exclusively for the female population. Background: The differences in biological, psychological and social characteristics, as well as the type of work carried out by men and women, make it necessary for workplace health promotion to be specific for each group. This study focussed on working women. Introduction: Workplace health promotion interventions are centred on increasing the well-being and health of the employees. Occupational health n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Additionally, the included studies were not tailored to the characteristics of the participants, who were predominately female and had a relatively high average age, as none of the included interventions addressed gender issues or took a life course approach. This result is in line with the findings of Jiménez-Mérida et al (2021), which have shown that the proportion of publications on workplace health promotion measures aimed specifically at women is very low (1.9%). Gender-related interventions that address specific aspects of women’s health throughout working life, such as premenstrual syndrome and breastfeeding in younger ages, or menopause and reducing the risk of osteoporosis in older age, are urgently needed in the female-dominated work sector of home care (Crawford et al, 2016; Jiménez-Mérida et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the included studies were not tailored to the characteristics of the participants, who were predominately female and had a relatively high average age, as none of the included interventions addressed gender issues or took a life course approach. This result is in line with the findings of Jiménez-Mérida et al (2021), which have shown that the proportion of publications on workplace health promotion measures aimed specifically at women is very low (1.9%). Gender-related interventions that address specific aspects of women’s health throughout working life, such as premenstrual syndrome and breastfeeding in younger ages, or menopause and reducing the risk of osteoporosis in older age, are urgently needed in the female-dominated work sector of home care (Crawford et al, 2016; Jiménez-Mérida et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…This result is in line with the findings of Jiménez-Mérida et al ( 2021), which have shown that the proportion of publications on workplace health promotion measures aimed specifically at women is very low (1.9%). Gender-related interventions that address specific aspects of women's health throughout working life, such as premenstrual syndrome and breastfeeding in younger ages, or menopause and reducing the risk of osteoporosis in older age, are urgently needed in the female-dominated work sector of home care (Crawford et al, 2016;Jiménez-Mérida et al, 2021). The inadequate tailoring of interventions may be related to the lack of participation of home care workers in the development of the interventions, as the present review identified only one study using a participatory approach.…”
Section: Discussionmentioning
confidence: 99%
“…Paid maternity leave is a key policy with significant impacts on breastfeeding prevalence and duration, although disparities in access and utilization persist (Andres, 2016; Nandi et al, 2018). Upon returning from paid leave, a broader package of supportive workplace policies and practices that include lactation spaces and breaks for milk expression were most effective (Jiménez‐Mérida et al, 2020; Tang et al, 2021) rather than just focusing on single policies. Research highlighted that broader organizational and interpersonal changes are necessary to achieve equitable working conditions for breastfeeding mothers (Vilar‐Compte et al, 2021) (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…via the debate relating to menstrual leave policies), 7 workplace occupational health promotion interventions rarely include gynaecological health awareness or free sanitary products. 8 Yet, menstruation is associated with sickness absence (time away from work) and presenteeism (productivity loss while at work), 9 so there are economic implications for employers. Furthermore, menstruation impacts negatively on students’ academic performance.…”
Section: A Gap In Policy and Practice For Workplaces And Universitiesmentioning
confidence: 99%